Light-Induced Tyrosine Radical Formation from Ruthenium-Tyrosine Complex Anchored to SnO2 Semiconductor - Raed Ghanem (International Journal of Photoenergy)
Steady state spectroscopy and flash photolysis measurements were used to study the multistep electron transfer in a supramolecular complex adsorbed on the surface of nanocrystalline SnO2 in order to mimic the function of the tyrosineZ and chlorophyll unit P680 in natural photosystem II (PSII). A ruthenium(II)-tris(bipyridyl) complex covalently linked to an L-tyrosine ethyl ester through an amide bond was anchored to the surface of nanocrystalline SnO2 via four carboxylic acid groups linked to the bpy ligands. The apparent association constant for the association between ruthenium(II)-tris(bipyridyl) complex and SnO2 is 3.2×106M−1 and a degree of association up to 99% was determined. 450 nm excitation of the complex promotes an electron to a metal-to-ligand charge transfer (MLCT) excited state, from which the electron is injected into SnO2. The photogeneration of Ru(III) is followed by an intramolecular electron transfer from tyrosine to Ru(III), regenerating the photosensitizer Ru(II) and forming the tyrosyl radical. The tyrosyl radical is formed in less than 3 microseconds with a yield of 32%.